1936
DOI: 10.1037/h0059696
|View full text |Cite
|
Sign up to set email alerts
|

Activity after recovery from rickets.

Abstract: Freud has postulated traumata of a psychosexual nature early in the life of the individual as a cause for neurotic or psychoneurotic disorders. This study was undertaken in order to ascertain other possible etiologic factors for such disorders. We wished to approach the problem from the standpoint of what damage might accrue to the psychobiologic makeup of the individual if early in his life cycle he had become conditioned by foods defective in certain elements: whether, for example, in addition to the skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1947
1947
1947
1947

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a very suggestive paper Ziegler and Knudsen (124) showed that young white rats fed on a rachitic diet during infancy ran less after recovery from the rickets than normals. If, however, the rats were deprived of Vitamin D at an even earlier age by feeding the rachitic diet to their mothers during pregnancy, the surviving pups were more active after recovery than normals.…”
Section: Vitaminsmentioning
confidence: 99%
“…In a very suggestive paper Ziegler and Knudsen (124) showed that young white rats fed on a rachitic diet during infancy ran less after recovery from the rickets than normals. If, however, the rats were deprived of Vitamin D at an even earlier age by feeding the rachitic diet to their mothers during pregnancy, the surviving pups were more active after recovery than normals.…”
Section: Vitaminsmentioning
confidence: 99%